Pengaruh Pengembangan Karir, Kompetensi dan Kepuasan Kerja Terhadap Kinerja Kantor Badan Pusat Statistik Kota Kediri - Okta Wahyu Ayuningtyas (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to determine the influence of career development variables (X1), competency (X2) and job satisfaction (X3) on employee performance (Y) at the Central Statistics Agency Office. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the study was 34 respondents at the Central Statistics Agency Office. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= -0.915 + 0.472X1 + 0.394X2 + 0.947X3 and the t test results of the variables career development, competence, job satisfaction had a partially significant effect on employee performance. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that career development, competence, job satisfaction have a simultaneous and significant effect on the performance of employees at the Central Bureau of Statistics.